2015
DOI: 10.1155/2015/283630
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects and Resistant Regulation of Magnolol and Honokiol on Methicillin-ResistantStaphylococcus aureus

Abstract: The antimicrobial killing activity toward methicillin-resistant Staphylococcus aureus (MRSA) has been a serious emerging global issue. In a continuing search for compounds with antibacterial activity against several microorganisms including S. aureus and MRSA, an n-hexane extract of Magnolia officinalis was found to contain magnolol. This compound exhibited potent activity against S. aureus, standard methicillin-susceptible S. aureus (MSSA), and MRSA as well as clinical MRSA isolates. When combined with oxacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Lignans, mainly honokiol and magnolol, have marked dose-dependent antimicrobial effects (Table 11) (Kim et al, 2015). Previous studies have shown that phenolic compounds can affect microbial growth by altering microbial cell permeability and permitting the loss of macromolecules.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Lignans, mainly honokiol and magnolol, have marked dose-dependent antimicrobial effects (Table 11) (Kim et al, 2015). Previous studies have shown that phenolic compounds can affect microbial growth by altering microbial cell permeability and permitting the loss of macromolecules.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Antibacterial activity of some of these hits had been reported before, e.g. for honokiol [93,94], MK-886 and 5-nonyloxytryptamine [80], but for most of the hits there were no previous indications for potential use as an anti-infective. Also four antipsychotic phenothiazine drugs (fluphenazine, perphenazine, thioridazine and trifluoperazine) and the antidepressant sertraline were hits.…”
Section: Repurposing Candidates With Potentiator Activitymentioning
confidence: 95%
“…The bactericidal non-microbial natural products are derived from various sources including, plants, insects, animals, and fungi. These natural compounds have been reported to target and act on multiple bacterial targets such as cell wall [62,63], pyruvate kinase [64], cell division [65], DNA topoisomerase [66], and efflux pump [67,68]. These pharmacological targets are further discussed in Section 4.…”
Section: Potent Natural Products Against Drug-resistant S Aureusmentioning
confidence: 99%